2021
DOI: 10.3389/fresc.2021.764686
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Enalapril Administration and Novel HIIT Wheel-Bed Training in Aged Rats

Abstract: Introduction: Growing research suggests that aerobic high-intensity interval training (HIIT) improves cardiovascular function and physical performance compared with moderate intensity continuous training (MICT). However relatively few animal models of HIIT are available to inform about the benefits of this exercise—particularly among older animals. In addition, there is little evidence for how HIIT training interacts with adjuvant pharmacological therapies known to enhance the impact of MCIT in older individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The LACE trial and a meta-analysis of available randomised controlled trials did not identify any effect of ACEi on muscle mass or strength (33), one possible reason for this is that the trial did not combine pharmacological treatment with exercise. In support of this possibility some studies have suggested that exercise responses are larger in patients taking ACEi than in those not taking ACEi [67] and some but not all animal studies have shown a that ACEi increases the gains from exercise [68,69]. However, several randomised control trials of exercise have not found support for this proposal.…”
Section: Plos Onementioning
confidence: 99%
“…The LACE trial and a meta-analysis of available randomised controlled trials did not identify any effect of ACEi on muscle mass or strength (33), one possible reason for this is that the trial did not combine pharmacological treatment with exercise. In support of this possibility some studies have suggested that exercise responses are larger in patients taking ACEi than in those not taking ACEi [67] and some but not all animal studies have shown a that ACEi increases the gains from exercise [68,69]. However, several randomised control trials of exercise have not found support for this proposal.…”
Section: Plos Onementioning
confidence: 99%